Insilico screening of newly synthesized spiro-1,2,4- Thiadiazoles for oral activity - RAJALA SRIKALA,; MEDEPALLI NARAYANA BABU, (International Journal of Pharma and Bio Sciences, 2017)
1,2,4-thiadiazoles are known to possess varied biological activities like antibacterial, antifungal, antiviral, anti-inflammatory, cardiovascular, antidiabetic, anticancer, antipsychotic, antiplatelet, antidepressant etc. For sixteen compounds N-[3-chloro-2-oxo-1-(substituted)-5-thia-1,6,8-triazaspiro[3.4]oct-6-en-7-yl]acetamide(5a – 5b) and 3-chloro-7-[3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl]-1-(substituted)-5-thia-1,6,8-triazaspiro[3.4]oct-6-en-2-one(5c – 5p) in a set, Lipinski parameters were calculated. The chemical structures which were drawn in DS Viewer Pro Suite and given as input and desired Lipinski parameters were selected. These studies were carried out using DS Accord for Excel (ADME screening) provided by Accelrys Discovery Studio software. Parameters were calculated based on the chemical structure. From the results, all the derivatives except 5e, 5f and 5g obey all the limits and thus meet the criteria for Lipinski's rule of five and are likely to be orally active. All the calculated parameters solely depend on the chemical structure of the derivatives and determine their oral activity.